simplify : 8 ( 5√2+1 ) / (√2+1 )² – ( √2–1 )²
( don't give unnecessary answers ) ( give correct answer only )
Attachments:
![](https://hi-static.z-dn.net/files/dec/6e7e7287cc77bcd470ba3efc96ac4238.jpg)
Answers
Answered by
1
Step-by-step explanation:
please mark me as brainlisy
Attachments:
![](https://hi-static.z-dn.net/files/db7/c3eb898a8bfa876e07a6a2257e35e44a.jpg)
Answered by
2
Given that
Hence,
More Identities to know:
- (a + b)² = a² + 2ab + b²
- (a - b)² = a² - 2ab + b²
- a² - b² = (a + b)(a - b)
- (a + b)² = (a - b)² + 4ab
- (a - b)² = (a + b)² - 4ab
- (a + b)² + (a - b)² = 2(a² + b²)
- (a + b)³ = a³ + b³ + 3ab(a + b)
- (a - b)³ = a³ - b³ - 3ab(a - b)
Similar questions
English,
2 months ago
Math,
2 months ago
Social Sciences,
4 months ago
English,
4 months ago
Science,
11 months ago